ANALISIS FAKTOR PENDORONG MINAT BELI PRODUK MATCHA DI PASAR URBAN - Orlandy, Altius; Rozan, Fico Devara; Wiryawan, Marcellino Tantyo; Noel, Marcia; Simatupang, Parhimpunan (POLITEKNIK LP3I JAKARTA, 2026)
This study aims to examine the factors influencing consumers’ purchase intention toward matcha beverages in Indonesia’s urban market using the Theory of Planned Behavior (TPB) framework. The variables analyzed include Perceived Quality, Perceived Value, Social Influence, and Service Convenience, with Attitude, Subjective Norms, and Perceived Behavioral Control acting as mediating constructs. A quantitative survey method was employed, collecting data from 208 Generation Z and Millennial respondents in the Greater Jakarta area. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 4 software. The results indicate that Perceived Quality and Perceived Value have a positive and significant effect on Attitude, while Social Influence significantly affects Subjective Norms. Service Convenience was found to positively influence Perceived Behavioral Control. Furthermore, Attitude and Subjective Norms significantly affect purchase intention, whereas Perceived Behavioral Control does not show a significant effect. The model demonstrates a moderate explanatory power for purchase intention. These findings suggest that consumers’ intention to purchase matcha beverages is primarily driven by attitudinal evaluation and social legitimacy rather than perceived behavioral control.